ON JUST, JUSTICE AND DISTRIBUTIVE JUSTICE: A CRITICAL AND COMPARATIVE DISCOURSE - Sooraj Kumar Maurya (Journal of Liberty and International Affairs, 2022)
Despite being endlessly debated, a unanimous impetus on the nature of just, justice, and distributive justice appears entirely untouched to the desirable scientific certainty so far. Aristotle asserts treating’ equals equally and un-equals unequally’ but in proportion to their relevant differences. John Rawls says 'justice as fairness.' To both Aristotle and John Rawls, justice meant for the good and a willingness to act by the laws to ensure the highest good of society. Antecedently, both agree that justice is a master imperative for good human relationships and coexistence. However, despite the universal agreement, they differ in many fundamental respects. Aristotle denies the outbound distribution of an individual's rights as only the head of the family has the right to free speech in the family. But, Rawls distributes each right to the individual level. The paper attempts to discuss the similarities and dissimilarities in Aristotle's and John Rawls'ideas of just, justice and distributive justice. It has been argued that the aim of both philosophers was the same, i.e., to find out a theory of justice through which unity, harmony, virtue, and happiness can be attained to the fullest in a nation.